Extended application of test results for fire resistance and/or smoke control for doorsets, shutter and openable window assemblies, including their elements of building hardware. Fire resistance of hinged and pivoted timber doorsets and openable timber framed windows Part 3, (29th November 2022) - British Standards Institution,
No abstract available